Comment les élèves catégorisent leurs cours/enseignants. Étude des catégories opératives dans une classe de quatrième de l’enseignement agricole - Hélène Veyrac; Audrey Murillo; Julie Blanc; Philippe Sahuc (Recherches en Éducation)
In this exploratory research we mobilize a new tool, developed in the field of activity analysis which involves asking students individually, to categorize their different lessons. All the 13 – 14 year old agriculture students in the same class produced, according to their own criteria, categories of lessons/teachers on 4 occasions during the year. This study thus helps to understand how the students perceive their school environment. The initial results would suggest that for the students their lessons closely linked to the teacher who takes them. The item” lesson-teacher” appears. As the year progressed, results show an evolution in the lesson-teacher perception: initially centered on the subject, then the activity (classroom rules, student activities) and finally on the effects on the student (in terms of experiencing attraction/rejection). Categories relating to academic success and the effectiveness of the teachers are rarely evoked. A qualitative analysis of the categories produced by certain students reveals rationalities and traces of development that open up perspectives for research in connection with the study of categorizations.